ASTM E2931: A new standard for the limiting oxygen concentration of combustible dusts. Issue 2 (11th February 2015) - Dastidar, Ashok Ghose
Abstract : The National Fire Protection Agency (NFPA) has a standard on explosion protection systems, NFPA 69, which provides guidelines on effective inerting to prevent explosions. The standard specifies that for inerting to be effective the oxygen concentration must be kept below the Limiting Oxygen Concentration (LOC). It then goes on to specify that the ASTM International standard E2079 be used to establish the LOC. The shortcoming of this approach is that ASTM E2079 only applies to combustible gases and vapors and not combustible dusts. As a result of this deficiency ASTM International has just introduced a new standard, ASTM E2931, Standard Test Method for Limiting Oxygen (Oxidant) Concentration of Combustible Dust Clouds . This paper discusses the nuances of this standard and compares experimental results between the 20‐L chamber and the 1‐m 3 chamber. Differences in the test results between the vessels and between test methods may have safety ramifications to the end user of the data. The large variation present in the repeatability and reproducibility of the LOC means that the current common practice of using a 2% safety margin for particle inerting (the least stringent of the inerting methods) may be insufficient to ensure dust cloud explosion mitigation. It is possible that additional study and improved laboratory proficiency as the test standard matures will bring down these repeatability and reproducibility errors. Additionally, if LOCs are reported in Safety Data Sheets without accompanying information regarding the test method or test vessel size used, the mitigation strategy may not provide adequate protection. © 2015 American Institute of Chemical Engineers Process Saf Prog 35: 159–164, 2016